Novel primers drive accurate SYBR Green PCR detection of Listeria monocytogenes and Listeria innocua in cultures and mushrooms - Bo-eun Kim; Ravi Jothi; Da woon Kim; Dong Suk Park (Scientific Reports)
Abstract The close genetic resemblance between Listeria monocytogenes and Listeria innocua, combined with their presence in similar environments, poses challenges for species-specific detection in food products. Ensuring food safety through microbiological standards necessitates reliable detection of pathogens like L. monocytogenes and L. innocua throughout the food chain using appropriate analytical techniques. This study aims to develop, identify, and validate a SYBR Green qPCR-based genetic marker designed to detect L. monocytogenes and L. innocua. By performing a comparative analysis of the complete genome sequences of L. monocytogenes (ATCC 12392) and L. innocua (CFSAN044836), a unique gene region encoding a hypothetical protein with an LPXTG cell wall anchor domain (GCF_003031895.1) in L. monocytogenes and leucine-rich repeats (GCF_009648575.1) in L. innocua was identified. Primers targeting these specific region were designed and validated for their effectiveness in detecting L. monocytogenes/L. innocua using both conventional PCR and qPCR techniques. These primers exhibited high sensitivity and specificity in amplifying L. monocytogenes and L. innocua among different Listeria species. The sensitivity and specificity of the primers were further confirmed through standard curve analysis using three different templates: cloned DNA (as a positive control), genomic DNA, and bacterial cell suspension. Additionally, the primers were rigorously tested and validated for their accuracy in directly detecting the targeted strains in live enoki mushroom samples. This direct qPCR method offers significant advantages for the rapid and precise detection of L. monocytogenes and L. innocua, potentially enhancing the efficiency of diagnostic and monitoring processes within food and vegetable distribution systems.